Proceedings of International Symposium and Exhibition on Formation Damage Control 2006
DOI: 10.2523/97794-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Drawdown and Depletion in Sanding Wells: Predictive Models Compared With Data From the Statfjord Field

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractExperience of sand production from the Statfjord field has been systemized to be able to predict the effect of drawdown and depletion on sand production. The aim of the study is to determine how reservoir pressure depletion will influence the sand production and to determine how sand production will influence the maximum liquid production rates. Most wells produce according to a maximum acceptable sand production criterion. Field data based on more than 300 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…If sanding volumes were to increase and significantly limit well offtake rates, this would have large consequences on the economics of the late life project. The operator performed an extensive rock mechanical study and this concluded that liquid production rates from C&P wells would likely need to be reduced to unacceptable levels during the pressure depletion in order to maintain acceptable sanding volumes and erosion rates 10 . This led the operator to the conclusion that some form of mechanical sand control was required for the late life wells; with the understanding that this strategy would lead to an increased sensitivity to downhole scaling 9 and a requirement for preventative scale treatments.…”
Section: Sand Productionmentioning
confidence: 99%
“…If sanding volumes were to increase and significantly limit well offtake rates, this would have large consequences on the economics of the late life project. The operator performed an extensive rock mechanical study and this concluded that liquid production rates from C&P wells would likely need to be reduced to unacceptable levels during the pressure depletion in order to maintain acceptable sanding volumes and erosion rates 10 . This led the operator to the conclusion that some form of mechanical sand control was required for the late life wells; with the understanding that this strategy would lead to an increased sensitivity to downhole scaling 9 and a requirement for preventative scale treatments.…”
Section: Sand Productionmentioning
confidence: 99%
“…This limit may vary depending on well completion size and design, and is different for a subsea well to that of a TLP well. 2 Well failure Scenario…”
Section: Well Lifementioning
confidence: 99%